STRATEGI PENINGKATAN DAYA SAING BIDANG KEBUDAYAAN DI PROPINSI DIY - Amiluhur Soeroso; Wahyu Ariani; Y. Sri Susilo (Faculty of Economics and Business, Universitas Gadjah Mada, 2008)
This research aims to explore cultural development indicators in Daerah Istimewa Yogyakarta (DIY), which seen having competitive advantage. Then, formulating its policy, strategy and implementation programs based on cultural development. Data were obtained from survey to inhabitants in four regencies and one city. We processed data statistically by factor and cluster analysis. In addition, we did SPACE (Strategic Position and Action Evaluation), internal-external analysis and using choice experiment to look for and chose priorities among them. The results indicate that imperative parameters of cultural shape are organic solidarity, spiritualism, social institution, introduction of Javanese culture and language on early education, appreciation of arts, using formal and non-formal institution simultaneous and doing well communication in society. Therefore, the critical factors of cultural physic are arts value, arts performance, supporting infrastructure of culture, heritage conservation, batik and lurik pattern, handicrafts, traditional fashion, discipline and caring Kraton as centre of Javanese culture. Consequently, government of DIY should push cognitive, affective and conative education and doing revitalization of tradition, custom and rituals that reflecting of identity, integrity and togetherness of Javanese ethnics.